Learning: What Should a Student Assess? - L. S. Grebnev (Высшее образование в России)
The article compares the educational aspects of student teaching assessment (STS) in traditional and “digital” technologies and considers the possibility of its application for the formation of universal managerial competencies of students instead of disciplinary action on teachers. To gain a better understanding of a problem of student teaching assessment, the author dwells on a conception of a pedagogical design, which is becoming the subject of students’ critical reflection. In the conditions of a total digitalization, the assessment criteria are changing, given that the students position themselves in a new managerial situation. From this perspective, assessment is viewed as a key managerial competence.